An ultrastructural study on corkscrew hairs and cigarette‐ash‐shaped hairs observed by dermoscopy of tinea capitis. Issue 2 (24th August 2015) - Lu, Mao; Ran, Yuping; Dai, Yaling; Lei, Song; Zhang, Chaoliang; Zhuang, Kaiwen; Hu, Wenying
Summary: This study was aimed to explain the formation mechanisms of corkscrew hairs and cigarette‐ash‐shaped hairs observed by dermoscopy of tinea capitis. In the present work, the ultrastructure of the involved hairs collected from a girl with tinea capitis caused by Trichophyton violaceum was observed by scanning electron microscope (SEM) and transmission electron microscope (TEM). SEM observation of the corkscrew hair revealed bent hair shaft and asymmetrically disrupted cuticle layer. TEM findings demonstrated the hair shaft became weak. The corkscrew hairs closely covered by scales on the scalp were observed under dermoscopy. We speculate that the formation of corkscrew hairs is a result of a combination of internal damage due to hair degradation by T. violaceum and external resistance due to scales covering the hair. SEM observation of the cigarette‐ash‐shaped hair revealed irregularly disrupted and incompact end, which might represent the stump of the broken corkscrew hair after treatment. SCANNING 38:128–132, 2016. © 2015 Wiley Periodicals, Inc.